GEOGRAFI DALAM PEMBELAJARAN STUDI SOSIAL ANAK USIA DINI: DALAM PERSPEKTIF KEBUTUHAN MEMBACA PETA DI ERA GLOBALISASI 5.0 - Aprilyanti, Dian Surya; Pertiwi, Citrabella (Tunas Siliwangi, 2025)
Geography learning in early childhood today is still limited to the introduction of places, various disasters and seasons or weather. The implementation of geography learning in early childhood has not yet reached the perspective of the needs of the 5'0 era of globalization. It can be seen from the low ability of Indonesians to read maps. This is known through the literacy survey of PISA 2022- 2023 results, which states that Indonesia is ranked 68 out of 81 countries in the world (Syamsul, 2023). While the development of technology and globalization today humans are very dependent on the use of digital maps in everyday life. This research aims to find out what kind of geography learning is implemented in early childhood. Has geography learning referred to the need to read maps in the era of Globalization 5'0, namely accommodating spatial understanding in children. The research method used is descriptive qualitative research method. The result of this research is that geography learning in early childhood has not been carried out in accordance with the needs of reading maps in the era of globalization 5.0. The need to read maps in geography learning is very close to early childhood. Where the use of gmaps is an application that is used massively everyday so that it must be introduced from an early age.